Answer: B. 8x+3y=5
-8x - 4y= -6
Explanation:
The given system of equations is expressed as
8x + 3y =5 - - - - - - - - -1
4x + 2y =3 - - - - - - - - - - 2
We would eliminate x by multiplying equation 1 by 4 and equation 2 by 8. It becomes
32x + 12y =20
32x + 16y = 24
Subtracting, it becomes
- 4y = - 4
y = - 4/ - 4
y = 1
Substituting y = 1 into equation 1. It becomes
8x + 3 × 1 =5
8x + 3 = 5 - 3 = 2
x = 2/8 = 1/4
Substituting x = 1/4 and y = 1 into the given options, it becomes
A. 8 × 1/4 + 3 × 1=5
2 + 3 = 5
- 8 × 1/4 +4 × 1 = 2
B. 8x+3y=5
-8x - 4y= -6
- 8 × 1/4 - 4 × 1 = -6
Therefore, the system of of equations that has the same solution as the given equation is
B. 8x+3y=5
-8x - 4y= -6